(3GdJCOjH haGYdjJg aj Jbhje GfMQGa GdehXa GdYGe aj GdfXGejf GdEOGQj GdhVYj hGdESdGej (B/s - (3YHO GdYGd, UHQj LdHj CMeOs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2014)
(3jJfGhd cJGH (B((3GdJCOjH haGYdjJg aj Jbhje GfMQGa GdehXa GdYGe aj GdfXGejf GdEOGQj GdhVYj hGdESdGej(B) (3hGdPj bGe HJCdjag (B"(3UHQj LHdj CMeO YHO GdYGd(B" (3aj MhGdj (B(174) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdhVY GdbGfhfj ddehXa(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3eaghe GdehXa GdYGe hVYG hTQYG, GdaUd GdKGfj (B: (3GdYbhHI GdJCOjHjI hVYG hTQYG, GdaUd GdKGdK (B: (3GdSdWGJ GdJCOjHjI hVYG hTQYG, GdaUd GdQGHY (B: (3GdVeGfGJ GdJCOjHjI hVYG hTQYG(B.s
(3HHdjhLQGajI (B: (3UaMI (B153-172.s
Keywords: (3GdehXahfs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3eUQs; (3GdehXahfs